Cyclic voltammetry insights into Ni/Al-carbonate hydrotalcite catalysis for methanol oxidation - Bushra Bari; Pawan Tyagi; Uche Udeochu (Scientific Reports)
Abstract The catalytic performance of Ni/Al-carbonate-based layered double hydroxide (Ni-LDH) for methanol oxidation reaction (MOR) was investigated using spectro-electrochemical techniques. Ni-Al hydrotalcite containing carbonate anions was synthesized and characterized by XRD, SEM, FTIR, and Raman spectroscopy. A glassy carbon electrode modified with Ni-LDH (NLGC) showed optimal catalytic activity under alkaline conditions (pH 13). Cyclic voltammetry (CV) of NLGC exhibited anodic and cathodic peak current densities at 0.62 V and 0.42 V, corresponding to quasi-reversible redox behavior of Ni(II)/Ni(III) centers. The linear correlation of peak current with scan rate in the non-faradaic region (0.1–0.3 V) suggests an adsorption mechanism involving the NiII-(OH)2/NiIII-OOH redox couple, while a square-root relationship indicates diffusion-controlled MOR. Hysteresis at 0.60 V and peak shifts further highlighted efficient charge transport, enhanced by the brucite layer of Ni-LDH. The electrochemically active surface area was calculated to be 0.042 cm², and linear sweep voltammetry revealed a 5.2 V onset potential. Double potential chronoamperometry confirmed a one-electron redox process, with a Tafel slope of 24.2 mV/dec. Raman analysis supported these findings, showing a redshift of NiII-O at 474 cm⁻¹ and formate ion vibrations, confirming NiIII-OOH’s role in MOR catalysis on NLGC.